(3GdEbJUGO GdEOGQj (B:s (3EbJUGOjGJ GdEOGQI GdESJQGJjLjI (B/s - (3GdWGFj, efi eMeO Ydjs ((3YeGf(B: s (3OGQ RgQGf ddfTQ hGdJhRjY(B, s, 2005)
(3CSGSjGJ aj GdEbJUGO GdEOGQj(B- (3UfY hEJNGP GdbQGQ aj GdXQha GdHjFjI GdeNJdaI(B- (3GdQHM hCgejJg defTCI GdCYeGd(B- (3GdQHM hGdEfJeGA GdShbj defTCI GdGYeGd(B- (3GdQHM hGMJcGQGJ GdbdI (B-(3WQhMGJ JHQjQ GdCQHGM(B- (3JbfjGJ aj EOGQI GdCQHGM(B- (3EOGQI GdWdH hEjQGOGJ GdefTCI(B- (3CgejI GdeQhfGJ aj GJNGP GdbQGQ(B- (3JMdjd GdfJGFL hJMdjd hEOGQI GdJcGdja(B- (3GSJQGJjLjGJ hCgOGa GdefTCI(B- (3ESJQGJjLjGJ hBdjGJGdJfGaS GdShbj(B- (3NjGQGJ GSJQGJjLjI hBdjGJ dJYRjR GdbOQGJ GdJfGaSjI(B.s
Keywords: (3GdEOGQIs; (3GdEOGQI GdESJQGJjLjIs; (3GdEbJUGOs; (3GdEbJUGO GdEOGQjs